Attitude and practices of personal protective equipment, telemedicine, and social distance among health care workers during COVID-19 pandemic: An international study - Dina Ali; Khaled Raafat; Rehab El-Sokkary (Microbes and Infectious Diseases, 2023)
Background: Coronavirus disease 2019 (COVID-19) pandemic is a huge burden on health systems worldwide. Healthcare workers (HCWs) are at the frontline in this battle and personal protective equipment (PPE) is a crucial element for their safety. Objectives: to assess the attitude and practices of PPE among HCWs alongside its availability and toxicities as well as to assess the use of telemedicine, physical barriers, and practice of social distance among HCWs. Methods: A cross sectional online survey was conducted between July and November 2020.  Healthcare workers from different countries were invited to participate via emails and social platforms. Results: Out of 384 requested to participate, 119 participants completed the survey. The mean age for the participants was 41.5± 10.4. Females accounted for (n=83, 69.8%). Although 67.2% said they received training for the correct use of PPE, a 69.7% and 79.8% failed to answer the correct order of donning and doffing PPE, respectively; (n=92, 77.3%) mentioned that N95/FFP2 respirators were the kind of masks routinely used for care of confirmed COVID-19 cases and (n=90, 75.6%) claimed that fit testing was done for N95/FFP2 respirators before use. Thirty-nine participants (n=39, 32.8%) said that they extended the use of PPE > 12 hours. Hazmat suit, overshoes, respirators, hair caps, and goggles were the most deficient PPE. The most frequently reported adverse events when working with PPEs were heat intolerance (47.1%), headache (43.7%), pressure areas (32.8%), and extreme exhaustion (31.1%). Regarding other protective measures, (n= 79, 66.4%) said they are maintaining adequate social distance; (n= 64, 53.8%) and (n=66, 55.5%) declared the use of physical barrier and telemedicine, respectively. As regard the attitude, a (n=79, 66.4%) said it is convenient to comply with the recommended PPE when examining COVID-19 cases. Conclusion: Donning and doffing were the most common PPE malpractices. There was a positive attitude towards PPE among the HCWs. There was limited access to telemedicine, physical barriers, and application of social distance inside the healthcare facilities.